Armel Shoes Enterprise : Safety Boot / Faten Nur Ameera Yanna Mohd Sailan ...[et al.] - Mohd Sailan, Faten Nur Ameera; Azmi, Farah Azmina; Basirun, Farah Wahidah; Suidi, Fatin Nabilah; Abd Jalil, Farah Syahira; Zulkifle, Eirin Sofia Zarith (2017)
Company which focuses on making innovation for the boots in order to make more comfortable and safe for people who wear it